OpenVM MOOC: un diseño para el aprendizaje autorregulado - Poce, Antonella; Amenduni, Francesca (Edutec, Revista Electrónica de Tecnología Educativa, 2021)
This paper presents the design of two miniMOOCs (Massive Open Online Courses) Autonomy-driven learning and Self-Regulated Learning (SRL), developed in the Open Virtual Mobility MOOC. The design is based on two concepts: microlearning and SRL. All the MOOC elements were designed to support SRL. From a descriptive and quantitative approach, the research aims to explore participants' satisfaction and their perception on the supporting roles of the miniMOOC for SRL. Data was collected through an online survey through which 375 answers were collected. Results show the general satisfaction of learners with the MOOC design. As for the SRL design gamification and visualization of pathways were more relevant for certain SRL phases such as monitoring learning. OER and related quizzes were useful for all SRL phases. Quizzes especially supported self-reflection. Open Badges supported the forethought phase of SRL. Social elements such as forums and eportfolios obtained the lowest rates in relation to support of SRL. The paper concludes with recommendations for educational research and MOOCs design.